2016
DOI: 10.1080/09638288.2016.1213898
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Arm Function in Multiple Sclerosis Questionnaire (AMSQ): a study based on Classical Test Theory

Abstract: The AMSQ shows satisfying results for validity and excellent reliability; allowing for proper use in research. Due to a large SDC value, caution is needed when using the AMSQ in individual patient care. Further research should determine whether the SDC is smaller than the minimal important change. Implications for Rehabilitation The Arm Function in Multiple Sclerosis Questionnaire (AMSQ) measures activity limitations due to hand and arm functioning in patients with Multiple Sclerosis (MS). Results of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…In our study, we found a lower correlation between the 9HPT and AMSQ ( r = 0.44–0.61) than in another study ( r = 0.77). 16 This supports the idea that different constructs were tested with the 9HPT and AMSQ. This is in line with our finding that combinations of movements explained different proportions of the variances of the 9HPT and AMSQ.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, we found a lower correlation between the 9HPT and AMSQ ( r = 0.44–0.61) than in another study ( r = 0.77). 16 This supports the idea that different constructs were tested with the 9HPT and AMSQ. This is in line with our finding that combinations of movements explained different proportions of the variances of the 9HPT and AMSQ.…”
Section: Discussionsupporting
confidence: 68%
“…2 The AMSQ is a unidimensional 31-item questionnaire with good psychometric properties. 3 However, a minimal clinically important difference (MCID) has not been reported yet. An MCID defines the smallest amount of change on a scale that is important or meaningful to a patient.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, the construct validity, test-retest reliability, and measurement error of the AMSQ were tested and were found sufficient. 16 As most studies in MS, either epidemiological studies or treatment trials, are performed in a multicenter international setting, outcome measures need to be available in all languages of the participating countries in trials. To that end, the AMSQ was translated into English, German, Spanish, French, and Italian.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, the construct validity, test–retest reliability, and measurement error of the AMSQ were tested and were found sufficient. 16…”
Section: Introductionmentioning
confidence: 99%